Medication management of autonomic nervous system disorders in adolescents with tuberculosis - L. А. Shovkun; N. Yu. Klimenko; V. А. Аksenova; D. А. Kudlay; N. Yu. Nikolenko; E. D. Kampos (Туберкулез и болезни лёгких, 2020)
To manage autonomic disorders in adolescents with tuberculosis, 100 people from 12 to 15 years old were examined and randomly divided into two groups: Group 1 received standard anti-tuberculosis therapy, and in Group 2, additionally to standard therapy, comprehensive treatment with Magne B6 was used for 2 months, and then Valerian extract was used for another 2 months. For comparison, 50 healthy adolescents were examined. Before treatment, all adolescents with tuberculosis experienced a decrease in heart rate variability, a pronounced autonomic imbalance with the prevalence of sympathicotonia and overexertion of compensatory mechanisms. In Group 1, during the comprehensive treatment there were an increase in SDNN and Mo and decrease in AMo and tension index at rest. Active orthostatic test (AOT) was accompanied by a significant increase in SDNN, Mo and a decrease in AMo, which indicated an increase in the activity of the parasympathetic autonomic nervous system and decreased activity of the sympathetic autonomic nervous system. In the group receiving standard therapy, hypersympathycotonia persisted and manifested through significant (p < 0.05) reduction in such parameters as SDNN, increased heart rate, AMo, and Mo shift to short intervals. Medication management resulted in the vegetative balance by increasing heart rate variability, reducing hypersympathicotonia, improving the autonomic support of the cardiovascular system at rest and during AOT.